GPRS-BASED MOBILE TELEMEDICINE SYSTEM - WOODWARD, BRYAN; RASID, M. FADLEE A.; GORE, LAWRENCE; ATKINS, PAUL (Journal of Mobile Multimedia, 2006)
An important emerging issue in mobile telemedicine, or m-Health, is how best to exploit the mobile communications technologies that are now almost globally available. This paper describes the design of a telemedicine system to transmit a patient’s biomedical signals to a hospital for monitoring or diagnosis, using a Bluetooth-enabled mobile telephone networked to the General Packet Radio Service (GPRS). The system can transmit from one to eight biomedical signals, typically including the electrocardiogram, blood pressure, temperature and oxygen saturation. The design of a database server that allows access to the received data by clinicians is also briefly described. The complete system has been tested successfully using several different data-enabled “smart” mobile telephones running on the Series 60 development platform. The tests were carried out while stationary and while travelling at high speed in a car.